Pengaruh Hedonic Shopping Motives dan Social Media Product Browsing terhadap Online Impulse Buying Produk Fashion pada Gen-Z di Pangkalpinang - Pratama, Vigo; Agung Nugroho, Ari; Yusnita, Maya (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research is motivated by a shift in people's consumption behavior that leads to consumptive behavior towards impulsive purchases online. This study aims to identify and analyze studies on the influence of hedonic shopping motives and social media product searches on impulse buying of fashion products online among Gen-Z in Pangkalpinang. This research is a quantitative descriptive study with a total sample of 130 respondents, sampling using non-probability sampling method with purposive sampling technique. The analytical method used is multiple linear regression analysis. The results of research on hedonic shopping motives and social media product browsing partially have a positive and significant effect on online impulse buying of fashion products for Gen-Z in Pangkalpinang. Simultaneous test results show that hedonic shopping motives and searching for social media products together have a positive and significant effect on the impulse to purchase online fashion products for Gen-Z in Pangkalpinang.